Relaciones de Consecuencia Lógica Supraclásicas y Filosofía de la Ciencia - Morales Delgado, Jorge (2026)
This paper examines the distinction between the context of discovery and the context of justification in the philosophy of science, in light of the philosophical and epistemological assumptions underlying supraclassical logical consequence relations. Two supraclassical formal systems are studied: non-monotonic logics and adaptive logics, and it is argued that these formalizations allow for a reconsideration of the limits and scope of the debate sparked by the distinction between contexts. The paper concludes by recognizing the importance of this contextual distinction, while emphasizing that this debate cannot overlook the development of contemporary logic.